Connectivity of Suborbital Graphs for the Congruence Subgroups of the Extended Modular Group
Let Γ be the extended modular group acting on Q by linear fractional transformation. In this paper, we investigate connectivity of the suborbital graphs F _u,n for the congruence subgroup Γ_0(n) of Γ ., number=3, journal=Communications in Mathematics and Applications, author=Jaipong, Pradthana and Tapanyo, Wanchai, year=2017, month=Dec., pages=345–358